(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Agritourism in Latvia is experiencing rapid growth, offering a unique opportunity to experience rural lifestyle and natural diversity. In addition to traditional agricultural activities, agritourism farms offer tourism services, thus diversifying their sources of income. The agritourism product corresponds to farms that preserve the traditions of agriculture, fishing, crafts and food production, while educating visitors and providing an opportunity to enjoy the beauty of nature, plant diversity and animal behavior. Agritourism is developing rapidly in Latvia because the countryside is rich in natural resources and ecological diversity. The aim of the study is to investigate and analyze the types of agritourism and their potential in Latvia, identifying the main trends and opportunities. The theoretical basis of the study is based on the study of various sources of information, supplemented with findings from studies and practical examples over several years. The study defined: the keywords characterizing agritourism: "Rural environment. Crafts. Recreation. Health. Nutrition", types of agritourism by purpose: agricultural, educational, gastronomic, health, recreational agritourism. Agritourism is a natural fit for Latvia's landscape, culture, and business traditions. Agritourism activities and services are diverse, including not only accommodation and meals, but also farm tours, educational and inclusive participation in farm work, master classes in making crafts and traditional art objects, traditional cooking from local products and their tasting, nature hikes, fishing, horseback riding and other forms of active recreation.